2021
DOI: 10.18046/recs.i35.4879
|View full text |Cite
|
Sign up to set email alerts
|

Mujeres, teletrabajo y estrategias de cuidados en el contexto de pandemia en Chile

Abstract: La pandemia de COVID-19 ha impactado a la población en distintas dimensiones, aumentando las desigualdades. Además de los efectos en la economía y la salud, se observan transformaciones en la cotidianidad, como la masificación del teletrabajo. Este hecho ha implicado una convergencia del espacio doméstico y el laboral, afectando en gran medida a las madres trabajadoras, quienes han aumentado su carga de trabajo de cuidados, impactando sus rutinas y su salud mental. El principal objetivo del presente artículo e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…This is possibly due to the fact that women preferred to work at home to take care of their children, since at the time of the pandemic schools and day care centres remained closed. Which is supported by various studies where they mention that females (70.3%) have a greater burden of domestic work and childcare than males (21.9%) [16,17].…”
Section: Discussion Of Resultsmentioning
confidence: 74%
“…This is possibly due to the fact that women preferred to work at home to take care of their children, since at the time of the pandemic schools and day care centres remained closed. Which is supported by various studies where they mention that females (70.3%) have a greater burden of domestic work and childcare than males (21.9%) [16,17].…”
Section: Discussion Of Resultsmentioning
confidence: 74%
“…In an indepth study of working women in different jobs, Arteaga-Aguirre et al (2021) argued that women were affected by the "simultaneous double presence in times of coronavirus, which leads women to intensify simultaneity as a strategy to address the different demands." They mention that female teachers have been particularly affected by this during COVID, given the demands of leading a classroom, attending to students, and working without fixed schedules all while addressing domestic responsibilities (Arteaga-Aguirre et al, 2021). Finally, studies have shown that structural inequalities present across the education system contributed towards mental health declines in Chile.…”
Section: Teachersmentioning
confidence: 99%
“…In Chile, the possibility of working remotely was more common for highly educated groups, those living in the Metropolitan District, and women [19]. In this regard, both national and international evidence show that the challenge of balancing the demands of the workplace with an increased domestic and caregiving workload was particularly marked for mothers [20,21].…”
Section: Covid-19 As a Stressful Event For Parentsmentioning
confidence: 99%